Anthropo-biological Theoretical Model of Teenage pregnancy of José Corona - José Luis Corona Lisboa (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
This article describes an explanatory theoretical model of adolescent pregnancy in 3 succinct postulates, the product of 8 years of research in the field of sexuality in adolescents. However, the ideas of other models prior to this one were taken into account, which served as the basis for impregnating other ideas that allow a more described adolescent pregnancy phenomenon. This model is not universal, since the behavior of adolescents is heterogeneous and varies according to the context in which it operates and the decision making regarding their sexuality.